2021
DOI: 10.1002/pa.2617
|View full text |Cite
|
Sign up to set email alerts
|

Covid‐19 pandemic: Current scenario and public risk perception in Pakistan

Abstract: Covid-19 is a Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2), which has exposed the issue of public risk perception among people in Pakistan. Previous research about public risk perception among people in Pakistan has been a neglected area till the writing of the current paper. The study aims to determine the level of public risk perception among people in Pakistan about the Covid-19 pandemic. Why and how public risk perception among health professionals and literate is more than the illiterate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Covid among the poorer people in developed countries (Wolf et al, 2020) and low risk perception among illiterate people in rural Pakistan (Gul, 2021). We note that government agencies designed awareness campaigns to educate the masses about the virus as soon as the pandemic started.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Covid among the poorer people in developed countries (Wolf et al, 2020) and low risk perception among illiterate people in rural Pakistan (Gul, 2021). We note that government agencies designed awareness campaigns to educate the masses about the virus as soon as the pandemic started.…”
Section: Discussionmentioning
confidence: 97%
“…People who were aware had better attitudes and practices indicating the importance of awareness in dealing with epidemics and pandemics (Alahdal et al, 2020). Earlier research has shown a lack of awareness regarding Covid among the poorer people in developed countries (Wolf et al, 2020) and low risk perception among illiterate people in rural Pakistan (Gul, 2021). We note that government agencies designed awareness campaigns to educate the masses about the virus as soon as the pandemic started.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding risk perception towards COVID-19, respondents to the first survey in 2021 have a generally high-risk perception. During these periods, Indonesia, Pakistan, and Turkey likewise indicated a high-risk perception of the transmission of the virus ( Gul, 2021 ; Tejamaya et al, 2022). However, the global immunisation programme decreased the risk perception of contracting the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The NCC set national policy which was implemented by the National Command and Operation Centre (NCOC) that was co-headed by the military and civilian leadership [30]. The NCOC coordinated the management of the extensive lockdowns, other key NPIs such as school closures, limited opening hours for essential businesses (examples of which included grocery stores and pharmacies), closure of borders, cancellation of public events and social gatherings [31,32]. This was supported based on an elaborate data gathering and analysis system that guided daily decisions.…”
Section: Plos Onementioning
confidence: 99%